UNRESOLVED CHILDHOOD TRAUMA IN MIKE FLANAGAN’S GERALD’S GAME MOVIE - Nieske Tiara Sabila; Much Khoiri (PARADIGM: Journal of Language and Literary Studies, 2021)
This article will analyze Gerald's Game movie, directed by Mike Flanagan. Issues arise regarding the effects or consequences that arise and affect a person's life after experiencing a trauma in childhood and how to deal with unresolved trauma. Jessi, the main female character, is sexually abused as a teenager by her biological father, which traumatizes her into adulthood.  The purpose of this article is to analyze how much influence trauma experienced in childhood can affect a person's personal life. This study uses a psychoanalysis approach based on Sigmund Freud's psychoanalytic theory. This article used direct quotations dialogs between characters from Gerald's Game movie. The findings show that the main character's reaction to a traumatic event and how she copes with it, although the event's memory is still attached to her.